2016
DOI: 10.1371/journal.pone.0158030
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Very Early Stepping Verticalization Protocol in Severe Acquired Brain Injured Patients: A Randomized Pilot Study in ICU

Abstract: Background and ObjectiveVerticalization was reported to improve the level of arousal and awareness in patients with severe acquired brain injury (ABI) and to be safe in ICU. We evaluated the effectiveness of a very early stepping verticalization protocol on their functional and neurological outcome.MethodsConsecutive patients with Vegetative State or Minimally Conscious State were enrolled in ICU on the third day after an ABI. They were randomized to undergo conventional physiotherapy alone or associated to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 36 publications
1
83
0
11
Order By: Relevance
“…Nevertheless, a small number of studies have investigated the effect of advanced technology training on consciousness in this population. The majority of these studies investigated the effect of advanced robotic tilt tables and found a positive effect on consciousness and cognition [11,15]. The effect of robotic gait training on consciousness has not been studied as intensively.…”
Section: Early Therapy Onsetmentioning
confidence: 99%
“…Nevertheless, a small number of studies have investigated the effect of advanced technology training on consciousness in this population. The majority of these studies investigated the effect of advanced robotic tilt tables and found a positive effect on consciousness and cognition [11,15]. The effect of robotic gait training on consciousness has not been studied as intensively.…”
Section: Early Therapy Onsetmentioning
confidence: 99%
“…In their article, the study authors used a nonparametric Mann‐Whitney U test (also known as the Wilcoxon rank‐sum test) to compare the improvements in treatment and control groups [7]. With this test, they found a nonsignificant difference between the 2 groups with a P value of .058, which is larger than the P value obtained with the randomization test.…”
Section: Example Results and Comparison With Published Resultsmentioning
confidence: 99%
“…Box plot of original data from Frazzitta et al [7]. Note that values are computed here so that positive scores indicate a decrease (improvement) in disability between baseline and discharge from the intensive care unit.…”
Section: Data Examplementioning
confidence: 99%
See 1 more Smart Citation
“…Blood pressures and heart rate can be stabilized better with treatment with passive leg movements [8]. Moreover, an intensive cyclic leg loading verticalization protocol, started in the acute stages of a severe acquired brain injury, improves the short-term and long-term functional and neurological outcome of patients with disorder of consciousness [9].…”
Section: Introductionmentioning
confidence: 99%